Quality of life and associated factors among children with cochlear implants in Vietnam: Results from parents' perception - Tran My Huong; Nguyen Dang Vung; Xuong Tuyet Nguyen (Elsevier, 2022)
Objective: This study was to assess the quality of life (QoL) of Vietnamese children with cochlear implants (CI) according to the perception of their parents, and to determine associated factors on the perceived QoL. Methods: A cross - sectional study were conducted among 68 children (20 children aged 3-6 years, and 48 children aged 7-10 years) who had cochlear implantation at the Vietnam National Children's Hospital, Hanoi, from June 2020 to November 2021. Kiddy-KINDLR and KINDLR questionnaires were used to gather information on QoL of their children. Scores were transformed to a 100-point scale with 100 representing the most positive response. Results: Parents of the 7-10 year group rated generic QoL more positively than the 3-6 year group, overall average scores were 72.1, and 69.6, respectively. Parents of 7-10 years also rated QoL of their children slightly below average than that of the standard hearing population in both girls, and boys. A significant inverse correlation was detected between the overall QoL and age at first cochlear implant (r = −0.284, p = 0.019), and duration of cochlear implant experience was positively correlated with overall mean QoL score (r = 0.268, p = 0.027). Higher level of father's education level showed better QoL among their children (p = 0.015). Conclusion: The QoL of Vietnamese children with CI were slight lower than average compared with normal hearing children. Age at cochlear implant, cochlear implant use duration, and education level of father were influencing factors of the QoL of children with CI in Vietnam.